ANALISIS JEJARING SOSIAL UNTUK MANAJEMEN PENGELOLAAN PERBATASAN ANTARA NEGARA - Ady Muzwardi; Adji Suradji Muhammad; Rolly Maulana Awangga; Arjuna Rizaldi (Prodi Ilmu Pemerintahan FISIP Universitas Komputer Indonesia, 2020)
The Province of Riau Islands is one of the provinces that have borders with neighboring countries, thus became the window of Indonesia. Therefore, the management in border areas will be a barometer state management of border in Indonesia in general. The current government has formed border management agency between countries starting from central government, Province to District/City level since Riau Islands share a border with 4 (four) foreign countries. Therefore, proper inter-country border management is expected to run optimally. However, there are still various problems from illegal activities such as smuggling, piracy, illegal fishing/mining, drugs, terrorism, etc. These problems should be solved by Collaborative Governance approach between stakeholders involved in the management of border areas. To find out how the parties are then this research will analyze how the involvement between parties with Social Networking approach. Keywords: collaborative governance, social networking, border area, management, governance